Как Муравьишка домой спешил: сказки / Виталий Бианки ; художник Б. Проказов - Бианки Виталий Валентинович (Колобок, 2006)
Экземпляры: ДБ/11/12/14/15/16/17/19/20/21 (20250116) / Инвентарный номер: 42416 / Цена: 41.40 / Сис.шифр: Р2мл / Авт.знак: Б 59 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6